The Nut - Carli, Philip (Flicker Alley, 2008)
Douglas Fairbanks, Sr. was making the transition from modern romantic stories to adventures when "The Nut" was made - The Mark of Zorro was the picture before this one, and The Three Musketeers would come after. He doesn't do as many of his famous stunts here, either - he suffered a serious injury while jumping out a window in one scene and production had to be halted while he healed. This no doubt forced him to slow down, and at some point between this picture and the mid-1920s he secretly began using a double for some stunts (actor/stuntman Richard Talmadge was the man used). The title character that Fairbanks plays is Charlie Jackson, a Greenwich Village character who invents Rube Goldberg-style contraptions. He uses them to please his friends and his sweetheart, Estrell Wynn but more often than not, they backfire. Estrell, who lives in his apartment building, wants to benefit slum children by having them entertained with the help of New York's biggest society names. This gives Jackson a new project to undertake; to get publicity he steals a load of wax statues from a show and is pursued by cub reporter Pernelius Vanderbrook. A gambler who lusts after Estrell tricks her into coming to his apartment. Jackson saves her from being compromised and helps her escape by taking her through the furnace pipes of the building. Featured in the story is a lawn party where Fairbanks is imitating a number of famous figures, one of them being comedian Charles Chaplin. This was actually the real Chaplin (a good pal of Fairbanks') parodying himself. Supposedly, Chaplin did all the other imitations, too. [www.rottentomatoes.com]
Keywords: DVD-Video